Propofol Exposure in Pregnant Rats Induces Neurotoxicity and Persistent Learning Deficit in the Offspring - Ming Xiong; Jing Li; Hussain M. Alhashem; Vasanti Tilak; Anuradha Patel; Sergey Pisklakov; Allan Siegel; Jiang Hong Ye; Alex Bekker (Brain Sciences, 2014)
Propofol is a general anesthetic widely used in surgical procedures, including those in pregnant women. Preclinical studies suggest that propofol may cause neuronal injury to the offspring of primates if it is administered during pregnancy. However, it is unknown whether those neuronal changes would lead to long-term behavioral deficits in the offspring. In this study, propofol (0.4 mg/kg/min, IV, 2 h), saline, or intralipid solution was administered to pregnant rats on gestational day 18. We detected increased levels of cleaved caspase-3 in fetal brain at 6 h after propofol exposure. The neuronal density of the hippocampus of offspring was reduced significantly on postnatal day 10 (P10) and P28. Synaptophysin levels were also significantly reduced on P28. Furthermore, exploratory and learning behaviors of offspring rats (started at P28) were assessed in open-field trial and eight-arm radial maze. The offspring from propofol-treated dams showed significantly less exploratory activity in the open-field test and less spatial learning in the eight-arm radial maze. Thus, this study suggested that propofol exposure during pregnancy in rat increased cleaved caspsase-3 levels in fetal brain, deletion of neurons, reduced synaptophysin levels in the hippocampal region, and persistent learning deficits in the offspring.